Another Way of Seeing: Ecological Existentialism in Cortázar’s “Axolotl” - Voelkner, Krysten (The Trumpeter, 2021)
This study provides a reading of Julio Cortázar’s short story “Axolotl” through the dual lenses of ecocriticism and mid-century existentialism. Specifically, the critical perspective of this work is inspired by the writings of existentialist philosopher Jean-Paul Sartre, and German biologist Jakob Johann von Uexküll. Such an interdisciplinary approach is intended to articulate a unique ecological perspective known as environmental existentialism. This critical approach not only acknowledges the longstanding influence that the existentialist movement has had on environmental scholarship, but also suggests that existentialist concepts are especially relevant to our contemporary ecological moment, and thus should continue to be employed in current ecological discourse. The primary locus of critical attention in this work centers on Sartre’s theory of the Look, Uexküll’s notion of the search tone, and Cortázar’s emphasis on suffering. These concepts are examined in concert to suggest that the correlations between the dominant issues of existentialist thought and our contemporary moment ought to signal to readers the existential threat that the age of the Anthropocene poses, as well as the value of reading texts both old and new through the lens of existential ecocriticism.